DNA targeting by Clostridium cellulolyticum CRISPR-Cas9 Type II-C system - Fedorova, Iana; Arseniev, Anatolii; Selkova, Polina; Pobegalov, Georgii; Goryanin, Ignatiy; Vasileva, Aleksandra; Musharova, Olga; Abramova, Marina; Kazalov, Maksim; Zyubko, Tatyana; Artamonova, Tatyana; Artamonova, Daria; et al. (Nucleic Acids Research, 2020)
Type II CRISPR-Cas9 RNA-guided nucleases are widely used for genome engineering. Type II-A SpCas9 protein from Streptococcus pyogenes is the most investigated and highly used enzyme of its class. Nevertheless, it has some drawbacks, including a relatively big size, imperfect specificity and restriction to DNA targets flanked by an NGG PAM sequence. Cas9 orthologs from other bacterial species may provide a rich and largely untapped source of biochemical diversity, which can help to overcome the limitations of SpCas9. Here, we characterize CcCas9, a Type II-C CRISPR nuclease from Clostridium cellulolyticum H10. We show that CcCas9 is an active endonuclease of comparatively small size that recognizes a novel two-nucleotide PAM sequence. The CcCas9 can potentially broaden the existing scope of biotechnological applications of Cas9 nucleases and may be particularly advantageous for genome editing of C. cellulolyticum H10, a bacterium considered to be a promising biofuel producer.
© The Author(s) 2020. Published by Oxford University Press on behalf of Nucleic Acids Research.
Keywords: CRISPR-Associated Protein 9/chemistry; CRISPR-Cas Systems/genetics; Clostridium cellulolyticum/enzymology; Crystallography, X-Ray; DNA/chemistry; Gene Editing; Mutation; Nucleotide Motifs/genetics; RNA, Guide, CRISPR-Cas Systems/genetics; Streptococcus pyogenes/enzymology; Substrate Specificity